2022
DOI: 10.2147/opth.s362926
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of a New Water Gradient Biomimetic Monthly Replacement Spherical Contact Lens Material (Lehfilcon A)

Abstract: Purpose The objective of this study was to evaluate the safety and performance of the investigational lens, lehfilcon A, when worn in a daily wear modality and replaced monthly as compared to the commercially available comfilcon A contact lens. Methods This was a multicenter, prospective, controlled, double-masked, randomized, parallel-group clinical study with bilateral lens wear for 3 months. In all, 115 subjects completed the study (77 with test lehfilcon A and 38 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
(66 reference statements)
1
3
0
Order By: Relevance
“…Although elapsed SH-SCL use time is a determining factor in complication risks, some scientific trials confirmed increased bulbar redness after six hours of use [ 40 , 41 , 42 ]. In the current study, non-statistically significant changes in bulbar redness were observed after 30 days of use in 8 eyes and decreased in 16 eyes, and no changes were observed in 38 remaining eyes, which could be attributed to the last generation SH-SCL high oxygen permeability, as other researchers previously achieved [ 43 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 55%
“…Although elapsed SH-SCL use time is a determining factor in complication risks, some scientific trials confirmed increased bulbar redness after six hours of use [ 40 , 41 , 42 ]. In the current study, non-statistically significant changes in bulbar redness were observed after 30 days of use in 8 eyes and decreased in 16 eyes, and no changes were observed in 38 remaining eyes, which could be attributed to the last generation SH-SCL high oxygen permeability, as other researchers previously achieved [ 43 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 55%
“…The properties of the aggregation-inducing contact lens materials that trigger this response are unknown and would require future investigation, but this response could potentially be due to diminished water content or surface topography of the contact lens materials. Acanthamoeba prefers to exist at the interfaces between soil and water, and surfaces indicating a strong water-aversion ( Liang et al, 2022 ; Wesley et al, 2022 ) may trigger the protective response.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the lehfilcon A lenses demonstrated excellent visual acuity, optimal lens fitting characteristics, clean surfaces, high wettability, and low risk of adverse events after 3 months of lens wear. A more detailed evaluation is expected in the future …”
Section: Antifouling Properties On Biomimetic Silicone Hydrogel Conta...mentioning
confidence: 99%